LIVING HERITAGE IN A CHANGING WORLD - Liu, Xuanlin. Link ([S.l.])
1 online resource
Keywords: The book explores living heritage through nomadic heritage in Inner Mongolia, China. Using a critical heritage approach, it examines how heritage is understood and enacted within changing communities and shifting lifestyles, revealing the dynamic nature of nomadic cultural heritage.The book critically re-examines nomadic heritage, capturing socio-cultural transformations and engaging in an ontological inquiry into living heritage. By bridging theory and practice, as well as tangible and intangible heritage, it redefines heritage's intrinsic logic in a changing world. Focusing on the ger, a dwelling central to Mongolian nomadic life, it analyses the continuity and transformation of ger practices. Using ethnographic research, it highlights the human-material-environment dynamic and the agency of multiple stakeholders in shaping heritage.This work is a key contribution to living heritage and nomadic heritage studies, offering valuable insights for scholars, professionals and those interested in nomadic culture.